Monogenic features of urolithiasis: A comprehensive review - Kyo Chul Koo; Abdulghafour Halawani; Victor K.F. Wong; Dirk Lange; Ben H. Chew (Asian Journal of Urology)
Objective: Urolithiasis formation has been attributed to environmental and dietary factors. However, evidence is accumulating that genetic background can contribute to urolithiasis formation. Advancements in the identification of monogenic causes using high-throughput sequencing technologies have shown that urolithiasis has a strong heritable component. Methods: This review describes monogenic factors implicated in a genetic predisposition to urolithiasis. Peer-reviewed journals were evaluated by a PubMed search until July 2023 to summarize disorders associated with monogenic traits, and discuss clinical implications of identification of patients genetically susceptible to urolithiasis formation. Results: Given that more than 80% of urolithiases cases are associated with calcium accumulation, studies have focused mainly on monogenetic contributors to hypercalciuric urolithiases, leading to the identification of receptors, channels, and transporters involved in the regulation of calcium renal tubular reabsorption. Nevertheless, available candidate genes and linkage methods have a low resolution for evaluation of the effects of genetic components versus those of environmental, dietary, and hormonal factors, and genotypes remain undetermined in the majority of urolithiasis formers. Conclusion: The pathophysiology underlying urolithiasis formation is complex and multifactorial, but evidence strongly suggests the existence of numerous monogenic causes of urolithiasis in humans.